Design of RM Infantry Robot Based on ROS System - Li, Yunxi (Journal of Theory and Practice of Management Science, 2025)
Based on the original Robomaster infantry robot, this paper designs an infantry robot based on the ROS system, so that the ROS-based Jetson nano and PC can undertake more tasks. In this paper, an infantry robot control system based on the ROS software framework is designed; the robot prototype is built and tested, and the sensor module (PTZ IMU) is extended on the Jetson nano. The results show that the basic functions of the robot are realized and the design requirements are met.